KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI - MOCHAMMAD SYAFIUDDIN SHOBIRIN; Patoni, Achmad; Maunah, Binti; Maksum, Moh. Ja'far Sodiq (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2023)
The study aims to test the relationship between transformational leadership and organizational commitment. The research uses a quantitative approach by collecting data through questionnaires distributed to respondents consisting of members of organizations at various levels of hierarchy. The analytical method used in this study is regression analysis to test the relationship between transformational leadership variables and organizational commitments. Research findings show a positive link between transformational leadership and organizational commitment. These findings show that transformational leadership styles that involve inspiration, intellectual stimulation, motivation, and good behavioral modeling have a significant impact on the level of commitment of the organization’s members. Furthermore, the research also shows that the most influential elements of transformational leadership on organizational commitment are inspiration and motivation. This research provides a better understanding of the importance of transformational leadership in building strong organizational commitments. These findings can be the basis for organizations to consider the importance of developing and promoting transformational leadership styles in an effort to enhance the commitment of members of the organization. The practical implications of this research are the importance of transformational leadership training and development for organizational leaders to higher commitments from members of the organization.